The Little Book of Trees - Lipscomb, Barney (Journal of the Botanical Research Institute of Texas, 2024)
From the publisher: Packed with surprising facts, this delightful and gorgeously designed book will beguile any nature lover. Expertly written and beautifully illustrated throughout with color photographs and original color artwork, The Little Book of Trees is an accessible and enjoyable mini-reference about the world’s trees, with examples drawn from across the globe. It fits an astonishing amount of information in a small package, covering a wide range of topics—from tree anatomy, diversity, and architecture to habitat and conservation. It also includes curious facts and a section on trees in myths, folklore, and modern culture from around the world. The result is an irresistible guide to the amazing lives of trees.